Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XIX: 2014/2015 - Bulakh, Maria; Hummel, Susanne; Rave, Thomas (Aethiopica, 2017)
Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XIX: 2014/2015